Instilling Nationalist Attitudes Through PPKN Learning in Class Vll Students of MTS Fatimah Nangapaang Manggarai Regency - santika, ita; Azis, Abdul; Syahrir, Musdalifah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Instilling Nationalism Attitudes Through PPKn Learning for Grade VIII Students of MTS Fatimah Nangapaang, Manggarai Regency. Nationalism is an attitude that must exist and be instilled early on in students in order to foster students to become good citizens, have knowledge, skills, and social concerns that are useful for themselves as well as society and the country. This study aims to determine the instillation of students' nationalism attitudes in subjects through PPKn subjects at MTS Fatimah Nangapaang, Manggarai Regency. This study is a type of qualitative field research by describing and analyzing the results of instilling nationalism attitudes through PPKn subjects. For data analysis using descriptive analysis by reducing data, presenting data, then drawing conclusions. The results of the study show that: Instilling Nationalism Attitudes Through PPKn Learning in class VII students of MTS Fatimah Nangapaang, Manggarai Regency can be seen from the love of the homeland and nation, pride as an Indonesian nation, appreciating the services of heroes, accepting diversity, including through habituation, role models, providing contextual examples, learning through stories and media, such as pictures of heroes, the song Indonesia Raya and other national songs.